Sentinel lymph node biopsy in squamous cell carcinoma of the head and neck: 10 years of experience - ANTONIO, J.K. (Pacini Editore SpA, 2012)
Sentinel node (SN) biopsy of head and neck cancer is still considered investigational, and agreement on the width of the surgical sampling has not yet been reached. From May 1999 to Dec 2009, 209 consecutive patients entered a prospective study: 61.7% had primary tumour of the oral cavity and 23.9% of the oropharynx. SN was not found in 26 patients. Based on these data and definitive histopathological analysis, we proposed six hypothetic scenarios to understand the percentage of neck recurrences following different treatments Among patients with identified SN, 54 cases were pN+: 47 in SN and 7 in a different node. Considering the six hypothetic scenarios: "only SN removal", "SN level dissection", "neck dissection from the tumour site to SN level", "selective neck dissection of three levels (SND)", "dissection from level I to IV" and "comprehensive I-V dissection", neck recurrences could be expected in 6.5%, 3.8%, 2.18%, 2.73%, 1.09% and 1.09% of cases, respectively. SN biopsy can be considered a useful tool to personalize the surgical approach to a N0 carcinoma. The minimum treatment of the neck is probably dissection of the levels between the primary tumour and the level containing the SN(s). Outside the framework of a clinical study, the best treatment can still be considered SND.